Overview of the Cause of Death of the Forensic Section of DR M.Djamil Hospital, Padang in 2019 - Mega Miftahul Rizka; Rika Susanti; M Fadil (Journal of Midwifery, 2021)
Backgrounds: Death eventually occurs in all living things. Statistical data of deaths are needed to determine policies, priorities, and development of health programs in order to improve health service provisions.